Trends in twitter : who, what, why? - Nurul Syafiqah Sapnan (2019)
Twitter has emerged to be one of the real-time means of information and people all over the world have been using that platform not only for communication but a way to know what is hot or trending. The trending topics were being determined by combination of volume and the time it takes to create such volume. Topics that are trended will appear at the left side of Twitter interface and users will be redirected to a new page should they click at a certain trend that appears on the list of tweets. However, this can be simplified in which users are able to easily know the rationale behind the trending topic by implementation of tooltip. Hence, in this paper, the methodologies to address who, what or why a certain topic was being trended on Twitter will be outlined. In order to retrieve and extract the data, this required further analytical thinking as to which tools or search engines are being widely used by users to obtain the required information. To enhance and improve on the relevance of the trending topic, successful extraction of information provided by different Application Programming Interfaces (APIs) such as Wikipedia, Google Custom Search and Twitter Standard Search API will be utilized.